Calcium isotopic fractionation during adsorption onto and desorption from soil phyllosilicates (kaolinite, montmorillonite and muscovite). (1st April 2019) - Brazier, Jean-Michel; Schmitt, Anne-Désirée; Gangloff, Sophie; Pelt, Eric; Chabaux, François; Tertre, Emmanuel
Abstract: Mineral soil constituents play an important role in the storage/release of nutrients due to their ability to adsorb and desorb cations. Phyllosilicate minerals are particularly reactive due to their small size and high specific surface area (up to ∼800 m 2 ·g −1 ). Previous work has highlighted the potential of Ca isotopes (δ 44/40 Ca) to identify secondary processes occurring within soils. Nevertheless, the mechanisms of isotopic fractionation (amplitude and nature) associated with Ca adsorption onto and desorption from different phyllosilicate minerals that are commonly found in soil remain poorly understood. This step is fundamental to improve our understanding of the Ca biogeochemical cycle at the water-soil-plant interface. Consequently, the study of the possible Ca isotopic fractionation during adsorption/desorption phenomena was approached experimentally using three "model" substrates representative of the phyllosilicate minerals frequently encountered within soils (KGa-2 kaolinite, Swy-2 montmorillonite and Tuftane muscovite). The experiments were carried out under abiotic conditions in "water-mineral" batch systems by precisely controlling the physico-chemical conditions: pH, solid/solution ratio, initial dissolved Ca concentration, particle size distribution, reaction time and other cations concentrations. Our results show no significant isotopic fractionation associated with Ca adsorption or desorption during KGa-2 and coarse size fraction of Tuftane muscovite (50–200 µm) experiments regardless of the physico-chemical parameters used. During Ca adsorption onto Swy-2 and fine size fraction of Tuftane muscovite (0.1–1 µm), light isotopes (e.g., 40 Ca) are preferentially adsorbed to the clay mineral, and a positive apparent isotopic fractionation between 0.10‰ and 0.28‰ is measured in the supernatant recovered after adsorption experiments. Kinetic and thermodynamic isotopic fractionation are observed during the Swy-2 experiments while only a thermodynamic fractionation took place during the Tuftane muscovite (0.1–1 µm) experiments. The results obtained for the Ca desorption experiments performed with a chloride hexaamine cobalt solution suggest that Ca adsorption and the associated isotopic fractionation are fully reversible. Our results show that the Ca isotopic fractionation intensity during adsorption phenomena onto clay minerals is controlled by the layer charge and specific surface area of the considered phyllosilicate mineral, as well as the presence of an interlayer space open to cationic solute.